Journey through genius : the great theorems of mathematics - Dunham, William (New York : John Wiley & Sons, Inc., 1990)
A rare combination of the historical, biographical, and mathematical, Journey through Genius is a fascinating introduction to a neglected field of human creativity. Now William Dunham gives them the attention they deserve. Dunham places each theorem within its historical context and explores the very human and often turbulent life of the creators - from Archimedes, the absent-minded theoretician whose absorption in his work often precluded eating or bathing to Gerolamo Cardano, the sixteenth-century mathematician whose accomplishments flourished despite a bizarre array of misadventures
Chapter1. Hippocrates' quadrature of the Lune (ca. 440 B.C.) -- Chapter2. Euclid's proof of the Pythagorean Theorem (ca. 300 B.C.) -- Chapter3. Euclid and the infinitude of primes (ca. 300 B.C.) -- Chapter4. Archimedes' determination of circular area (ca. 225 B.C.) Chapter5. Heron's formula for triangular area (ca. A.D. 75) -- Chapter6. Cardano and the solution of the cubic (1545) -- Chapter7. A gem from Isaac Newton (late 1660s) -- Chapter8. The Bernoullis and the Harmonic series (1689) -- Chapter9. The extraordinary sums of Leonhard Euler (1734) -- Chapter10. A sampler of Euler's number theory (1736) -- Chapter11. The non-denumerability of the continuum (1874) -- Chapter12. Cantor and the transfinite realm (1891) .
Includes bibliographical references
Keywords: BIOGRAPHIES; HISTORY